Effectiveness of Single Dose Povidone Iodine Sclerotherapy for the Treatment of Chyluria - Islam, Md Shahidul; Islam, Md waliul; Islam, Ahm Manjurul; Hossain, Md Anwar; sultana, Parveen (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the effectiveness of single dose 5 % povidone iodine renal pelvic instillation sclerotherapy for the treatment for chyluria. Methods: In a prospective study from January 2009 and till June 2013, 47 patients presenting with milky urine (chyluria and hematochyluria) were included. Patients with other co-morbid illness like diabetes, urinary infection, renal stone disease, chronic pyelonehritis were excluded from the study. Apart from ether test, the presence of lymphocytes in urine and urine triglycerides levels were also done to confirm chyluria. Under local anesthesia, cystoscopic evaluation revealed right-sided efflux in 11 (23.4%), left-sided in 36 (76.6%), and no bilateral involvement was detected. 5F open-ended ureteric catheter was introduced in the ureteric orifice of affected side. Freshly prepared 10 ml of 5 % povidone iodine solution was instilled over a minute with the patient in Trendelenburg position. Results: Total of 47 patients were enrolled (26 males and 21 females; mean age 41 years, SD 8.4, range 29–71) with a mean follow-up of 12 months. Immediate clearance was seen in all patients and recurrence in 9 (19.15 %). Overall success rate 80.85%. Mean diseasefree duration was 12 months. Three patients had moderate to severe flank pain. Conclusion: Single dose 5 % povidone iodine sclerotherapy is a effective treatment for chyluria. As the patients discharged on the next day after procedure, it can be offered as a day care basis, so continuous ureteral and urethral catheterizations can be avoided. Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.74-78